2015
DOI: 10.1016/j.reprotox.2015.05.002
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation changes in the placenta are associated with fetal manganese exposure

Abstract: Adequate micronutrient intake, including manganese (Mn), is important for fetal development. Both Mn deficiencies and excess exposures are associated with later-life disease, and Mn accumulates in the placenta. Placental functional alterations may alter fetal programming and lifelong health, and we hypothesized that prenatal exposures to Mn may alter placental function through epigenetic mechanisms. Using Illumina’s HumanMethylation450 BeadArray, DNA methylation of >485,000 CpG loci genome-wide was interrogate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 81 publications
2
36
0
Order By: Relevance
“…Within each batch, samples with concentrations below the limit of detection were assigned a value equal to half of the lowest observed value in that batch. 21 Similar to previous reports from this study population, 22 the number of samples with concentrations below the minimal detection levels varied for each metal, ranging from 1% (Zn) to 68% (As).…”
Section: Metals Exposuresupporting
confidence: 68%
See 2 more Smart Citations
“…Within each batch, samples with concentrations below the limit of detection were assigned a value equal to half of the lowest observed value in that batch. 21 Similar to previous reports from this study population, 22 the number of samples with concentrations below the minimal detection levels varied for each metal, ranging from 1% (Zn) to 68% (As).…”
Section: Metals Exposuresupporting
confidence: 68%
“…Several recent epigenome-wide association studies have linked prenatal exposure to arsenic, mercury, cadmium, and manganese to methylation across several loci, [21][22][23][24][25][26][27][28] including sites related to central nervous system development and behavioral disorders. 21,22 Moreover, patterning in methylation at these sites was prospectively linked to poor infant neurobehavior 22 and lower birthweight, 21 both considered sentinels of later life cognitive and behavioral problems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A great body of literature has made efforts to understand what epigenetic variations can be induced by what environmental factors throughout the lifetime [12,2326]. In particular, with the growth of high-throughput technology, epigenome-wide studies allow us a holistic insight into the epigenetic programming in response to specific environmental factors [2731]. …”
Section: Introductionmentioning
confidence: 99%
“…The nuclear factor kappa-light-chain-enhancer of active B cell (NF-κβ) pathway is a major regulator of cytokine production and is affected by manganese [14, 15]. Additionally, previous human studies have shown that manganese is associated with changes in patterns of DNA methylation [16, 17] although no studies have examined the effects of manganese on epigenetic regulation of the NF-κβ pathway. To date, the inflammatory potential of dietary manganese intake or the effects of dietary manganese on DNA methylation have yet to be examined.…”
Section: Introductionmentioning
confidence: 99%